2015
DOI: 10.1017/s0033291715000471
|View full text |Cite
|
Sign up to set email alerts
|

Familial risk for distress and fear disorders and emotional reactivity in adolescence: an event-related potential investigation

Abstract: Background The late positive potential (LPP) is an event-related potential component that is sensitive to the motivational salience of stimuli. Children with a parental history of depression, an indicator of risk, have been found to exhibit an attenuated LPP to emotional stimuli. Research on depressive and anxiety disorders has organized these conditions into two empirical classes: distress and fear disorders. The present study examined whether parental history of distress and fear disorders was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 75 publications
9
71
0
Order By: Relevance
“…One caveat to this organization is that panic disorder appears to have features of both fear and distress, and has been found to load on both subfactors (Greene & Eaton, 2016;H. Kim & Eaton, 2015;Nelson et al, 2015;Watson et al, 2012;Wright et al, 2013). Also, OCD is a relatively weak member of the fear cluster and shows some overlap with the thought disorder dimension (Caspi et al, 2014;Chmielewski & Watson, 2008;Watson, Wu, & Cutshall, 2004).…”
Section: Subfactorsmentioning
confidence: 99%
“…One caveat to this organization is that panic disorder appears to have features of both fear and distress, and has been found to load on both subfactors (Greene & Eaton, 2016;H. Kim & Eaton, 2015;Nelson et al, 2015;Watson et al, 2012;Wright et al, 2013). Also, OCD is a relatively weak member of the fear cluster and shows some overlap with the thought disorder dimension (Caspi et al, 2014;Chmielewski & Watson, 2008;Watson, Wu, & Cutshall, 2004).…”
Section: Subfactorsmentioning
confidence: 99%
“…For example, Nelson, Perlman, Hajcak, Klein, and Kotov (2015) related neural measures of emotional reactivity to the distress and fear subfactors, and found that the former was associated with blunted neural reactivity to all stimuli, whereas the latter was associated with enhanced reactivity to negative stimuli specifically. Weinberg et al (2015) evaluated links between neural markers of error-processing and symptom components of the internalizing domain, and found that enhanced neural reactivity to errors was specifically associated with the checking component across various disorders.…”
Section: Research and Clinical Applications Of A Quantitative Classifmentioning
confidence: 99%
“…Cross-sectional research suggests the LPP may measure emotional processing styles that contribute to vulnerability for psychopathology. For example, offspring of parents with fear disorders (i.e., panic disorder, social anxiety disorder, and specific phobia) and children with fearful temperament showed enhanced LPPs to unpleasant stimuli (36; 37). In addition, blunted LPPs to emotional faces have been observed in youth at risk for depression based both on parental history of depression and temperament style (3739).…”
mentioning
confidence: 99%
“…For example, offspring of parents with fear disorders (i.e., panic disorder, social anxiety disorder, and specific phobia) and children with fearful temperament showed enhanced LPPs to unpleasant stimuli (36; 37). In addition, blunted LPPs to emotional faces have been observed in youth at risk for depression based both on parental history of depression and temperament style (3739). Importantly, there is evidence that individual differences in processing and coping with emotions contribute to children’s responses to stress (40), suggesting that the magnitude of the LPP may moderate effects of stress on the development of symptoms.…”
mentioning
confidence: 99%